2003
DOI: 10.1038/sj.onc.1206418
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of tumor suppression by destabilizing AU-rich growth factor mRNA

Abstract: The occurrence of pathologically stable mRNAs of protooncogenes, growth factors and cyclins has been proposed to contribute to experimental and human oncogenesis. In normal resting cells, mRNAs containing an AU-rich element (ARE) in their 3 0 untranslated region are subjected to rapid degradation. Tristetraprolin (TTP) is an RNA-binding zinc-finger protein that promotes decay of ARE-containing mRNAs. Here we report that TTP acts as a potent tumor suppressor in a v-H-ras-dependent mast cell tumor model, where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 41 publications
3
74
0
1
Order By: Relevance
“…Very recently, it has been reported that TTP acts as a potent tumour suppressor when overexpressed in a v-H-ras-dependent mast cell tumour model (Stoecklin et al, 2003). Our results would suggest that this effect could result from decreased VEGF mRNA levels and decreased angiogenesis.…”
Section: Discussionmentioning
confidence: 50%
“…Very recently, it has been reported that TTP acts as a potent tumour suppressor when overexpressed in a v-H-ras-dependent mast cell tumour model (Stoecklin et al, 2003). Our results would suggest that this effect could result from decreased VEGF mRNA levels and decreased angiogenesis.…”
Section: Discussionmentioning
confidence: 50%
“…The remaining members of the class have known tumor suppressor activities as well but do so through different mechanisms. Tristetraprolin (ZFP36L2) destabilizes growth factor mRNA and increases mRNA turnover (Stoecklin et al 2003) and microseminal protein b, MSMB or PSP94; one of the most highly expressed genes in porcine corpus luteum from our previous work; Jiang et al 2004) is an inhibitor of vascular endothelial growth factor (VEGF) signaling (Lamy et al 2005). Janus kinase 1 can have proliferative or antiproliferative properties depending on the nature the activating ligand (Verma et al 2003).…”
Section: Genbankmentioning
confidence: 99%
“…Such inhibitors might be of clinical importance in situations in which improper mRNA stabilization leads to overexpression of labile mRNAs, such as tumor necrosis factor ␣ overexpression in inflammatory disease (1,5) and proto-oncogene overexpression in cancer cells inappropriately expressing Hu proteins (34,35,47,68). Recent experiments in which TTP was overexpressed demonstrate that the modulation of mRNA decay can be used to suppress oncogenesis (67). This observation emphasizes the importance of understanding the interactions of proteins with the AREs of labile mRNAs, not only at a functional level but at the detailed mechanistic level, as well.…”
mentioning
confidence: 99%